Impact of the COVID-19 pandemic on youth delinquency: A discontinuous growth analysis - Li, Nan; Quintana, Diana; Shelton, Matthew; Grigorenko, Elena L. (Frontiers in Education, 2023)
Introduction This study aimed to investigate (a) the immediate and long-term changes in youth offending rates among 138 neighborhoods within a large metropolitan area in the context of COVID-19 and (b) the extent to which the socioeconomic composition of the neighborhoods accounted for variations of the changes. Methods Discontinuous growth models were applied to demonstrate the changes in offenses against a person, property offenses, and drug-related offenses one-year prior to, at (March 2020), and one-year following the pandemic. Results At the onset of the pandemic, we registered an immediate reduction in offenses against a person and property offenses but not in drug-related offenses. There was a steeper declining trend for property offenses one-year following the pandemic as compared with that one-year prior to the pandemic. The neighborhood concentration of affluence and poverty was not related to the immediate reduction in any type of delinquency. Discussion We conclude that the COVID-19 pandemic not only had an abrupt but also an enduring impact on youth delinquency.